Traditional Chinese Medicine for the Treatment of Diarrhea - Peng, Linying; Du, Xiaoquan (Journal of Contemporary Medical Practice, 2025)
Clinically, diarrhea can present either as an independent disease or as a symptom secondary to other illnesses. Owing to changes in people’s dietary habits and patterns, coupled with the impacts of high-pressure environments and fast-paced lifestyles, the incidence of this condition has been increasing annually. Notably, TCM has demonstrated unique advantages in alleviating clinical symptoms and providing preventive and rehabilitative care for diarrhea.